An introduction to executive compensation - Balsam, Steven (Academic Press, 2002)
General readers have no idea why people should care about what executives are paid and why they are paid the way they are. That's the reason that The Wall Street Journal, Fortune, Forbes, and other popular and practitioner publications have regular coverage on them. This book not only proposes a reason--executives need incentives in order to maximize firm value (economists call this "agency theory")--it also describes the nature and design of executive compensation practices. Those incentives can take the form of benefits (salary, stock options), perquisites (reflecting the status of the executive within the organizational culture.